A nano-multilayer porous structure intelligent controlled release coating for bone repair and a preparation method thereof
Patent Information
- Application Number
- CN202611059671.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-07-21
- Filing Date
- 2026-07-16
- Publication Date
- 2026-10-23
AI Technical Summary
[0007]针对现有钛基植入体存在药物控释与骨愈合阶段难协调、多功能涂层性能协同设计困难、促骨元素界面扩散行为机制不明、人体微环境下涂层易腐蚀磨损等技术难题,本发明提供了一种用于骨修复的纳米多层多孔结构智能控释涂层及其制备方法,通过对涂层结构设计、药物负载方式、元素扩散路径及膜基结合机制的系统优化,显著提升了涂层的抗菌性、促骨愈合性、耐磨蚀性及生物稳定性
1、本发明提出的一种用于骨修复的纳米多层多孔结构智能控释涂层,采用致密保护层、多层多孔药物承载层、促骨元素扩散层与Zr基阻隔层的复合结构设计,能够实现骨修复过程中药物的定向、分阶段精准释放,提升抗菌效率并协同促进成骨,从而实现骨缺损区域的高效修复与功能重建。
Smart Images

Figure CN122955023A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of medical coating technology, specifically relating to a nano-multilayer porous intelligent controlled-release coating for bone repair and its preparation method. Background Technology
[0002] Titanium and titanium alloys, due to their excellent biocompatibility, suitable mechanical properties, and good corrosion resistance, have been widely used in orthopedic implants for repairing bone defects, replacing bone tissue, and maintaining bone structural stability. With the aging population and the increasing incidence of bone metabolic diseases such as osteoporosis, the clinical demand for bone implant materials is growing. While titanium-based implants demonstrate good performance in initial use, several problems remain during long-term service, such as difficulty in actively inducing osteogenesis, susceptibility to infection at the implantation site, and susceptibility to corrosion and abrasive shedding on the material surface, limiting their effectiveness in repairing complex bone defects.
[0003] To enhance the overall performance of titanium-based implants in vivo, surface coating technology has become the primary modification method. By constructing multi-layered composite coatings with functions such as antibacterial properties, osteogenic properties, corrosion resistance, and wear resistance, the biocompatibility of the material with surrounding tissues can be effectively improved, and its stability in body fluid environments can be enhanced without altering the intrinsic properties of the substrate.
[0004] Currently, commonly used technologies for constructing coatings on titanium alloy surfaces include filtered cathodic vacuum arc deposition (FCVAD), controlled accelerated arc deposition (CAA-PVD), and sol-gel technology. Each method has its advantages: FCVAD offers high bonding strength, CAA-PVD balances film density and deposition efficiency, and Sol-Gel facilitates control over structural uniformity and porosity. However, a single process often struggles to simultaneously meet multiple performance requirements such as controlled drug release, interfacial bonding, and film quality, resulting in problems such as insufficient structural-functional coupling in the coating system, low interfacial bonding strength, and mismatch between drug release timing and other factors.
[0005] In recent years, multilayer functional coating systems have gradually become a research hotspot. By introducing a drug-carrying layer, a diffusion regulation layer, and an interface enhancement layer with a spatially hierarchical structure, not only can gradient controlled release and time-sequential release of drugs be achieved, but the synergistic effect of interface structural continuity and component interdiffusion can also be enhanced, significantly improving the bone healing effect and mechanical stability of the coating.
[0006] Meanwhile, to address the corrosion-wear coupling failure behavior commonly observed in titanium-based implants in bodily fluid environments, the use of alternating ceramic / metal structures, multiphase passivation layers, and nanocomposite reinforcement mechanisms can effectively delay failure modes such as coating peeling and crack propagation, thereby improving the long-term service capability of the implant. Therefore, constructing an integrated multifunctional coating system with high bonding strength, controllable drug release, and excellent corrosion and wear resistance will become a key technological path to solve the current performance bottlenecks of titanium-based implants. Summary of the Invention
[0007] To address the technical challenges of existing titanium-based implants, such as the difficulty in coordinating drug release with the bone healing stage, the difficulty in designing synergistic properties of multifunctional coatings, the unclear mechanism of interfacial diffusion of bone-promoting elements, and the susceptibility of coatings to corrosion and wear in the human microenvironment, this invention provides a nano-multilayer porous intelligent controlled-release coating for bone repair and its preparation method. Through systematic optimization of coating structure design, drug loading method, element diffusion path, and membrane-substrate binding mechanism, the antibacterial properties, bone-healing properties, wear resistance, and biostability of the coating are significantly improved.
[0008] To achieve the above objectives, the present invention provides the following technical solution: A nano-multilayer porous structure smart controlled-release coating for bone repair comprises the following five layers from the inside out: (1) Titanium alloy matrix; (2) Diffusion barrier layer; The diffusion barrier layer is a Zr-ZrN, Zr-ZrO2, Zr,Hf-(Zr,Hf)N or Zr,Hf-(Zr,Hf)O2 structure, which is mainly used to enhance the film-substrate bonding force, prevent titanium from diffusing into human tissue, and play a role in bonding and transitioning the substrate and the upper layer material. (3) Metal diffusion layer; The metal diffusion layer contains osteogenic active elements such as Ca, Mn, and Mg, which can be released through ion diffusion after the drug carrier layer degrades, and synergistically promote the formation and mineralization of new bone; (4) Multilayer porous biodegradable drug carrier layer; the multilayer porous biodegradable drug carrier layer is composed of a variety of responsive biodegradable materials, including pH-responsive chitosan, enzyme-responsive gelatin and oxidation-responsive sulfide polymer, and by regulating the degradation rate of the materials, the gradient release of drugs at different stages of bone repair can be achieved. (5) Dense, biodegradable, wear-resistant, and antibacterial drug protective layer, wherein the dense, biodegradable, wear-resistant, and antibacterial drug protective layer is composed of hydroxyapatite and antimicrobial peptides, possessing high hardness and good antibacterial properties, and can protect the drug from shear force and wear in the early stage of surgery, and reduce the risk of infection.
[0009] Preferably, the drug carrier layer has a multi-layer structure with different degradation materials arranged layer by layer, and its porous structure can improve the drug loading capacity and controlled release effect.
[0010] The coating system of this invention controls the drug release pattern and the diffusion path of bone-promoting elements through a multi-layer composite structure. While achieving intelligent controlled release, it significantly enhances the mechanical stability, wear resistance and biocompatibility of the coating, making it suitable for various titanium-based implant scenarios such as fracture fixation and bone defect repair.
[0011] A method for preparing a nano-multilayer porous structure smart controlled-release coating for bone repair, characterized by comprising the following steps: (1) Provide a surface-treated titanium alloy substrate; (2) A diffusion barrier layer is formed using filtered cathode vacuum arc deposition (FCVAD) technology; (3) A metal diffusion layer containing Ca, Mg, and Mn was deposited using a controlled accelerated arc deposition (CAA-PVD) process combined with filtered cathode vacuum arc deposition (FCVAD) technology; (4) A multi-layered porous drug-carrying layer was constructed using sol-gel technology and loaded with bone-healing drugs; (5) A dense and wear-resistant drug protective layer of hydroxyapatite / antimicrobial peptide is deposited by vacuum arc deposition to form the final multifunctional coating structure.
[0012] Preferably, in step (1), the titanium alloy substrate is ultrasonically cleaned with organic solvent and deionized water, and then dried.
[0013] Preferably, in step (2), a Zr-ZrN layer with a thickness of 480-500 nm is deposited on the surface of the titanium alloy substrate using FCVAD technology, at a temperature of 280-300 °C and a deposition time of 55-60 minutes.
[0014] Furthermore, the thickness is 500 nm, the temperature is 300 °C, and the deposition time is 60 minutes.
[0015] Preferably, in step (3), a Ca, Mg, and Mn metal diffusion layer with a thickness of 400 nm is deposited on the surface of the diffusion barrier layer using CAA-PVD combined with FCVAD technology, with a deposition current of 80-85 A, a magnetic field strength of 380-400 Gs, a deposition temperature of 280-300 °C, and a deposition time of 25-30 minutes.
[0016] Furthermore, the deposition current was 85A, the magnetic field strength was 400Gs, the deposition temperature was 300℃, and the deposition time was 30 minutes.
[0017] Preferably, in step (5), the dense layer is deposited using the FCVAD technique.
[0018] Compared with the prior art, the beneficial effects of the present invention are: 1. The present invention proposes a nano-multilayer porous intelligent controlled-release coating for bone repair, which adopts a composite structure design of a dense protective layer, a multilayer porous drug-carrying layer, a bone-promoting element diffusion layer and a Zr-based barrier layer. It can achieve targeted and phased precise release of drugs during the bone repair process, improve antibacterial efficiency and synergistically promote osteogenesis, thereby achieving efficient repair and functional reconstruction of bone defect areas.
[0019] 2. This invention significantly enhances the film-substrate bonding strength between the coating and the titanium alloy substrate by introducing metal diffusion barrier layers such as Zr-ZrN / ZrO2 into the coating structure, effectively alleviating stress concentration caused by lattice mismatch and thermal expansion differences, preventing coating peeling and cracking, and improving the service stability and lifespan of the implant.
[0020] 3. This invention uses biodegradable porous chitosan, gelatin and thioether polymers to construct a responsive drug-carrying structure, and combines it with bone healing-promoting drugs to dynamically regulate the bone healing microenvironment to precisely control the biological behavior of BMSCs, thereby promoting bone regeneration.
[0021] 4. The coating system of the present invention has significant advantages in terms of wear resistance and corrosion resistance. The dense protective layer effectively resists external friction damage and the penetration of corrosive media, significantly reduces abrasive wear and pitting risk, and improves overall biosafety.
[0022] 5. The multi-process deposition route using FCVAD, CAA-PVD, sol-gel, etc. adopted in this invention has the advantages of strong process versatility, adaptability to complex morphological substrates, good repeatability, and suitability for large-scale production, and has good potential for engineering and clinical application. Attached Figure Description
[0023] Figure 1 This is a schematic diagram of the structure of a nano-multilayer porous intelligent controlled-release coating for bone repair according to the present invention; Figure 2 This is a schematic diagram of another case of the nano-multilayer porous structure intelligent controlled-release coating for bone repair according to the present invention; Figure 3 This is a schematic diagram of the metal diffusion layer structure of the present invention; Figure 4 This is a schematic diagram of the multilayer porous biodegradable drug carrier layer structure of the present invention; Figure 5 Here are analytical diagrams of the structures of various parts in this invention; Figure 6 This is a cross-sectional SEM image of the (Zr,Cr)N diffusion barrier layer prepared by FCVAD technology in this invention. Figure 7This is a cross-sectional EDS energy spectrum of the (Zr,Cr,Al)N metal diffusion layer prepared by CAA-PVD combined with FCVAD technology in this invention. Figure 8 The image shows the characteristic spectrum of the (Zr,Cr,Al)N metal diffusion layer prepared by CAA-PVD combined with FCVAD technology in this invention. Figure 9 This is a cross-sectional SEM image of the (Zr,Cr,Al)N metal diffusion layer prepared by the CAA-PVD process in this invention. Figure 10 This invention presents a cross-sectional micro-region EDS of a (Zr,Cr,Al)N metal diffusion layer prepared using the CAA-PVD process. Detailed Implementation
[0024] To make the technical means, creative features, objectives and effects of this invention easier to understand, the following embodiments are described in detail with reference to the accompanying drawings. It should be noted that the description of these embodiments is for the purpose of helping to understand this invention, but does not constitute a limitation of this invention.
[0025] like Figure 1 , 2 As shown in Figure 5, a nano-multilayer porous structure intelligent controlled-release coating for bone repair includes a titanium alloy substrate 1. The surface of the titanium alloy substrate 1 is sequentially provided with a diffusion barrier layer 2, a metal diffusion layer 3, a multilayer porous drug carrier layer 4 (specifically a multilayer porous biodegradable drug carrier layer) and a dense drug protective layer 5 (specifically a dense biodegradable wear-resistant antibacterial drug protective layer). S1. Substrate pretreatment: Select a Ti-6Al-4V titanium alloy substrate with dimensions of 10×10×1 mm. Grind it sequentially with sandpaper (#600~#2000). Then, ultrasonically clean it with acetone, ethanol and deionized water for 15 minutes each. Place it in a vacuum drying oven and dry it at 80°C for 2 hours for later use.
[0026] S2. Deposition of diffusion barrier layer: Using FCVAD technology, a Zr-ZrN layer with a thickness of 500 nm is deposited on the surface of the titanium alloy substrate at 300 °C for 60 minutes. Specifically, using the titanium alloy substrate obtained in step S1 as the cathode, filtered cathode vacuum arc deposition (FCVAD) technology is used to deposit Zr-ZrN, Zr-ZrO2, Zr,Hf-(Zr,Hf)N, or Zr,Hf-(Zr,Hf)O2 composite structures in a vacuum chamber at a deposition temperature of 200–300 °C, a substrate bias voltage of -100–-200 V, and a deposition time of 90–120 min, resulting in a diffusion barrier layer with a thickness of 0.5–1.5 μm. S3. Preparation of the metal diffusion layer: A 400 nm thick Ca, Mg, and Mn metal diffusion layer was deposited on the surface of the diffusion barrier layer using CAA-PVD combined with FCVAD technology. The deposition current was 85 A, the magnetic field strength was 400 Gs, the deposition temperature was 300 °C, and the deposition time was 30 minutes. Specifically, on the substrate surface obtained in step S2, bone-promoting metal elements such as Ca, Mg, and Mn were deposited respectively using controlled accelerated arc physical vapor deposition (CAA-PVD). The deposition current was 80–120 A, the magnetic field strength was 300–600 Gs, the deposition temperature was 250–350 °C, and the time was 20–60 minutes, forming a metal diffusion layer with a thickness of 300–500 nm. S4. Construction of Multilayer Porous Biodegradable Drug Carrier Layers: Three biodegradable drug carrier layers with different response mechanisms were sequentially deposited using spin coating: a pH-responsive layer (chitosan-based), an enzyme-responsive layer (gelatin-based), and an oxidation-responsive layer (thioether polymer-based) sol. The spin coating parameters were set as follows: spin coating speed of 2500 rpm and spin coating time of 30 seconds. After each layer was deposited, it was dried at 60℃ for 1 hour to ensure film quality and porous structure stability, with a thickness of 1 μm. Specifically: Chitosan sol: Chitosan was dissolved in 1% acetic acid solution to prepare a 0.5% w / v sol; Gelatin solution: 1% w / v gelatin was dissolved in water at 40℃; Thioether polymer solution: An oxidation-responsive thioether polymer was dissolved in anhydrous ethanol to prepare a 5% w / v solution. S5. Construction of a dense, biodegradable, wear-resistant, and antibacterial protective layer: A dense layer was deposited using FCVAD technology. The prepared sample was placed in the FCVAD chamber, maintaining the substrate temperature at 150°C. Before deposition, a 15-minute Ar plasma bombardment cleaning was performed using a hydroxyapatite target, and a basic vacuum of 5 × 10⁻⁶ was maintained within the vacuum chamber. - ³ Pa, working gas is Ar, gas flow rate is 20 sccm. The deposition arc current is set to 65 A, and the bias voltage is... At 200 V, with a deposition time controlled at 15 minutes, a dense protective layer with a thickness of 0.8 μm can be obtained. Specifically, the three sols prepared in step (4) are sequentially coated onto the metal diffusion layer obtained in step (3) using a spin coating method. The spin coating speed for each layer is controlled at 1000–3000 rpm, and the spin coating time is 20–60 s, or the extraction speed is controlled at 50–300 μm / s. After each layer is formed, it is dried at 40–80 °C for 0.5–2 h. The multilayer structure is constructed alternately in sequence to finally form a porous drug carrier layer with a thickness of 1–1.5 μm. S6. Drug loading: Immerse the porous coating in the drug solution for 20-60 minutes, and then dry and fix the drug at low temperature; if it is necessary to increase the loading, the loading can be repeated 2-3 times.
[0027] S7. Deposition of the outer dense protective layer: The antimicrobial peptide is mixed with hydroxyapatite to form a sol system, and a dense layer is deposited using the FCVAD method. The deposition temperature is controlled at 80–200℃ to form a dense, biodegradable protective layer with a thickness of 0.8–1.5 μm, which is used for encapsulating drugs and enhancing antimicrobial properties and wear resistance.
[0028] S8. Post-treatment: The prepared multilayer composite structure is dried under vacuum at 60°C for 4-6 hours, or sterilized under sterile conditions with ultraviolet light for 30 minutes, and then cured by overall cross-linking at 120°C for 2 hours to finally complete the construction of the entire intelligent controlled-release coating system.
[0029] Furthermore, the coating system has the following multi-layer structure: including a titanium alloy substrate, a diffusion barrier layer, a metal diffusion layer, a multi-layer porous drug carrier layer, and a dense antibacterial protective layer.
[0030] Furthermore, each layer of the multilayer biodegradable drug carrier layer has a thickness of 100–600 nm, and the overall thickness is 1–1.5 μm.
[0031] Furthermore, the mass ratio of hydroxyapatite to antimicrobial peptide in the dense protective layer is 5:1 to 10:1, and the layer thickness is controlled between 0.8 and 1.5 μm.
[0032] like Figure 3 As shown in Figure 5, this embodiment provides a metal diffusion layer structure based on the metal diffusion mechanism. This structure, as an important component of the intelligent controlled-release coating, is located between the drug-carrying layer and the diffusion-blocking layer, and is designed to further promote bone regeneration in the mid-to-late stages of bone healing after drug release. The metal diffusion layer incorporates various osteogenic metal elements, including Ca, Mg, and Cu ions. These elements are uniformly introduced into the layer in an alloyed or co-deposited form, exhibiting a gradient distribution that gradually transitions from the drug carrier layer down to the substrate in the coating structure. Through the design of tissue diffusion behavior, Ca, Mg, and Cu elements can diffuse outward into the surrounding bone tissue after the drug carrier layer has gradually degraded, promoting osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) and new bone formation. The magnified view shown in the figure illustrates the microstructure of the metal diffusion layer: Cu atoms are distributed in the form of large particles on the surface of the diffusion path, while Mg and Ca atoms are interspersed in the interlayer, forming a multi-layered interlaced structure, which helps the elements to be slowly released in the tissue and prolongs the duration of their biological activity.
[0033] This metal diffusion layer not only helps to prolong the osteogenic effect after the drug delivery system terminates, but its structural stability and good mechanical bonding properties also enhance the overall structural integrity of the coating. As shown in Figures 4 and 5, this embodiment provides a multi-layer porous biodegradable drug-carrying layer. This structure is one of the core parts of the coating design of this invention. It has a highly ordered and controllable hierarchical structure, which can achieve efficient loading and time-sequential release of bone-promoting drugs.
[0034] The drug delivery layer is primarily composed of three types of responsive degradable materials, each sensitive to specific physiological stimuli to meet drug release requirements at different stages of bone healing: Layer A (upper layer): pH-responsive degradable layer, made of chitosan. When the local environment is slightly acidic in the early stages of fracture healing, this layer preferentially degrades, releasing initial drugs such as antioxidants (e.g., hydrosilene nanosheets) to scavenge ROS and protect BMSCs; Layer B (middle layer): Enzyme-responsive degradable layer, using gelatin as the matrix material. In the middle stage of bone healing, degradation is triggered by specific enzymes secreted by tissue (e.g., collagenase), gradually releasing drugs with pro-angiogenic and osteogenic activities; Layer C (lower layer): Oxidation-responsive degradable layer, composed of thioether polymers. During the recovery period from oxidative stress, it gradually oxidizes and degrades, continuously releasing drugs such as Si... 4+ Osteogenic factors, such as BMSCs, are used to promote the differentiation of BMSCs into osteoblasts. The three-layer structure incorporates porous channels to increase drug loading and coordinate release rates. The thickness and porosity of each layer can be adjusted according to clinical needs, thereby achieving precise controlled release and personalized treatment. This multi-layered, porous drug-carrying layer plays a crucial role in precisely delivering drugs at specific times within the overall coating system, providing continuous drug support for fracture healing that aligns with physiological changes.
[0035] Example 1 A diffusion barrier layer prepared using filtered cathode vacuum arc deposition (FCVAD) process; the main research focuses on the microstructure and defect control performance of the coating. This embodiment employs filtered cathode vacuum arc deposition (FCVAD) combined with a highly efficient separation system of a pulsed magnetic field evaporator (with a microdroplet removal rate exceeding 98%) to deposit a (Zr, Cr)N diffusion barrier layer on a metal substrate pretreated with mechanical polishing and ultrasonic cleaning. An Al (99.5% + 0.4% Si) cathode is installed in the FCVAD system, which features a unique high-energy flow and a structure that filters the droplet phase. During deposition, the working pressure inside the vacuum chamber is maintained at 0.66 Pa, the deposition temperature is 300–350 °C, the substrate bias voltage is -150 V, and the deposition time is 15 min.
[0036] Depend on Figure 6 The SEM cross-section shows that, at a magnification of 10000, the prepared diffusion barrier layer exhibits excellent thickness uniformity and continuity, with a tight film-substrate interface. Due to the unique magnetic filtration mechanism of the FCVAD process, large droplet phase particles in the plasma flow are effectively removed, resulting in an extremely smooth and dense nano-periodic superlattice microstructure. This clear and continuous nano-interlayer interface directly demonstrates that during low-pressure reactive deposition, the bombardment of special high-energy particle streams in the FCVAD process significantly enhances the surface diffusion ability of deposited atoms, thereby effectively suppressing the abnormal growth of coarse columnar crystals during deposition. This fundamentally ensures the excellent density, resistance to brittle fracture, and high bonding strength of the diffusion barrier layer.
[0037] Experiment Example 2 A metal diffusion layer prepared using controlled accelerated arc physical vapor deposition (CAA-PVD) combined with filtered cathode vacuum arc deposition (FCVAD) was investigated. The effects of the composite deposition techniques on the microstructure, density, and spatial distribution of characteristic elements of the metal diffusion layer were examined. In this embodiment, CAA-PVD and FCVAD are combined on a substrate surface that has been pretreated and has a barrier layer deposited.
[0038] The FCVAD system is equipped with a mass fraction of The system features an aluminum-silicon alloy cathode, possessing high-energy particle flux density and a magnetic separation microstructure for efficiently filtering microdroplet phases; simultaneously, a purity of [missing information] is installed on the CAA-PVD evaporator. metal cathode and purity of metal Cathode. High-purity nitrogen gas is introduced into the vacuum chamber. ( ) as the reactant gas, to achieve a working gas pressure of 2.00 Pa within the chamber. Before deposition, first turn on... The target is controlled with a deposition current of 65 A, and a DC negative bias of -1500 V is applied to the substrate. A high-energy plasma beam is used to powerfully bombard the substrate surface to achieve in-situ heating, deep ion etching, and secondary activation cleaning. Then, the coating deposition stage begins: the substrate turntable rotation speed is controlled at 0.7 rpm, and the deposition temperature is precisely maintained in the range of 300℃ to 350℃. During this process, the substrate bias voltage was fixed at -150 V, and the co-deposition time was 45 minutes; through Figure 7Energy-dispersive X-ray spectroscopy (EDS) was used to perform surface scanning analysis on the cross-section of the metal diffusion layer. This clearly revealed a distinct heterogeneous, layered, spatially hierarchical microstructure within the coating. Due to the synergistic effect of the efficient droplet blocking by FCVAD magnetic filtering and the precise release of thermal stress by CAA-PVD, longitudinal through-cracks and coarse metallic phase segregation, which are highly prone to occur in traditional high-current deposition, were effectively eliminated. The entire composite layer cross-section was dense, uniform, and continuous. Along the direction away from the substrate, the characteristic elements exhibited a benign compositional gradient that gradually transitioned from the inside out (the matrix layer, Zr-rich layer, and Al / Cr-rich layer were arranged in a sequential gradient layered pattern), demonstrating a clear nano-superlattice layered network. This provided excellent interfacial mechanical integrity and service stability for the entire composite coating system.
[0039] Figure 8 The EDS characteristic spectrum of the metal diffusion layer is shown in Table 1. Qualitative and quantitative analysis of the chemical composition of the coating micro-regions were performed. The test spectra were sharp and free from impurity signal interference. The quantitative analysis results of the core functional components in the micro-regions are shown in Table 1: Table 1: Quantitative Analysis Results of Characteristic Spectra of (Zr, Cr, Al) N Metal Diffusion Layers Transition components in the metal substrate of the coating It accounts for as high as 46.78% by weight (19.43% atomic percentage, core wear-resistant reinforcing component). The weight percentage is 29.38% (atomic percentage is 21.41%), while the amount introduced through FCVAD... The element's atomic percentage is stable at 5.79% when reacting with high concentrations of gas to form... The elements (53.37% atomic percentage) together constitute a highly dense multi-component nitride superlattice structure. This precise compositional matching and microstructure demonstrate that the CAA-PVD combined with FCVAD composite process described in this invention successfully achieves precise spatial hierarchical allocation of multi-functional elements at the nanoscale. This ensures that the active bone-promoting elements, after gradual degradation of the external porous drug carrier layer, possess excellent ability to diffuse and release sequentially, slowly, and for a long time into surrounding tissues. This allows for continuous regulation of the bone repair microenvironment during the mid-to-late stages of implantation, synergistically promoting new bone formation and mineralization.
[0040] Experimental Example 3 A metal diffusion layer prepared using controlled accelerated arc physical vapor deposition (CAA-PVD) was used as a control group in Experiment 2 to investigate the effect of a single deposition process without FCVAD on the purity and uniformity of the micro-region composition of the metal diffusion layer. In this embodiment, a metal diffusion layer is deposited on the surface of the barrier layer using the CAA-PVD process. Only Cr (99%) and Zr (99.98%) cathodes are installed on the CAA-PVD evaporator, and high-purity nitrogen gas is introduced to bring the gas pressure in the chamber to 2.00 Pa. All other process parameters, such as target current, bias voltage, substrate rotation speed, deposition temperature, and deposition time of 45 minutes, are completely consistent with those in Experimental Example 2.
[0041] Figure 9 The image shows a cross-sectional SEM of the metal diffusion layer prepared using CAA-PVD. As can be seen, the coating continuously covers the substrate surface, has a certain overall thickness, and forms an interfacial bonding region between the coating and the substrate. However, when prepared using a single CAA-PVD process, the interface between the coating and the substrate remains relatively clear, the metal transition layer is relatively thin, and no significantly wide diffusion zone is formed. Layered or columnar growth characteristics can be observed within the coating, indicating that the deposition process is still primarily a layer-by-layer growth mode dominated by physical vapor deposition.
[0042] pass Figure 10 EDS surface scanning analysis of the cross-section of the metal diffusion layer revealed that nitrogen (N) was mainly distributed in the coating region, while Zr and Cr were concentrated on the coating side, and Al was mainly distributed on the 7050 aluminum alloy substrate side. At the interface between the coating and the substrate, Zr, Cr, Al, and N exhibited a certain degree of overlap, indicating the formation of a metal element diffusion and interface transition region during deposition. Zr and Cr were mainly distributed on the coating side, while Al was mainly distributed on the substrate side, with some overlap near the interface. The elemental transition region between the coating and the substrate was relatively narrow, and the elemental distribution on both sides of the interface showed significant changes. Compared to coatings prepared using a combination of CAA-PVD and FCVAD technology, coatings prepared using a single CAA-PVD process exhibited a smaller elemental transition range at the coating-substrate interface, and the continuity of metal element distribution near the interface was relatively weak.
[0043] The above embodiments are preferred embodiments of the present invention and are not intended to limit the scope of protection of the present invention. Various modifications or variations that can be made by those skilled in the art without creative effort within the scope of the appended claims are still within the scope of protection of this patent.
Claims
1. A nano-multilayer porous structure intelligent controlled-release coating for bone repair, characterized in that, It includes the following layers arranged sequentially from the inside out: a titanium alloy substrate; A diffusion barrier layer, wherein the diffusion barrier layer comprises Zr-ZrN, Zr-ZrO2, ZrHf-(ZrHf)N or ZrHf-(ZrHf)O2; A metal diffusion layer containing one or more of Ca, Mn, and Mg, capable of diffusing outwards after implantation to promote bone repair; a multi-layered porous biodegradable drug-carrying layer comprising three biodegradable polymers: pH-responsive degradable material chitosan, enzyme-responsive material gelatin, and oxidation-responsive material sulfide polymer; and a dense, biodegradable, wear-resistant, and antibacterial drug protective layer comprising hydroxyapatite and antimicrobial peptides to improve hardness, prevent wear, and provide antibacterial properties.
2. The nano-multilayer porous structure intelligent controlled-release coating for bone repair according to claim 1, characterized in that: The drug-carrying layer has a multi-layered structure with different degradation materials arranged layer by layer. Its porous structure can improve the drug loading capacity and controlled release effect.
3. A method for preparing a nano-multilayer porous structure intelligent controlled-release coating for bone repair, characterized in that: Includes the following steps: (1) Provide a surface-treated titanium alloy substrate; (2) A diffusion barrier layer is formed using filtered cathode vacuum arc deposition (FCVAD) technology; (3) A metal diffusion layer containing Ca, Mg, and Mn was deposited using a controlled accelerated arc deposition (CAA-PVD) process combined with filtered cathode vacuum arc deposition (FCVAD) technology; (4) A multi-layered porous drug-carrying layer was constructed using sol-gel technology and loaded with bone-healing drugs; (5) A dense and wear-resistant drug protective layer of hydroxyapatite / antimicrobial peptide is deposited by vacuum arc deposition to form the final multifunctional coating structure.
4. The method for preparing a nano-multilayer porous structure intelligent controlled-release coating for bone repair according to claim 3, characterized in that: In step (1), the titanium alloy matrix is ultrasonically cleaned with organic solvent and deionized water, and then dried.
5. The method for preparing a nano-multilayer porous structure intelligent controlled-release coating for bone repair according to claim 3, characterized in that: In step (2), a Zr-ZrN layer with a thickness of 480-500 nm is deposited on the surface of the titanium alloy substrate using FCVAD technology at a temperature of 280-300 °C for a deposition time of 55-60 minutes.
6. The method for preparing a nano-multilayer porous structure intelligent controlled-release coating for bone repair according to claim 3, characterized in that: In step (3), a Ca, Mg, and Mn metal diffusion layer with a thickness of 400 nm is deposited on the surface of the diffusion barrier layer using CAA-PVD combined with FCVAD technology. The deposition current is 80-85 A, the magnetic field strength is 380-400 Gs, the deposition temperature is 280-300 °C, and the deposition time is 25-30 minutes.
7. The method for preparing a nano-multilayer porous structure intelligent controlled-release coating for bone repair according to claim 3, characterized in that: In step (5), dense layer deposition is performed using FCVAD technology.
